What are the reasons for unfinished nursing care as perceived by hospitalized patients? Findings from a qualitative study - Stefania Chiappinotto; Alberto Coppe; Alvisa Palese (Wiley, 2023)
Abstract Introduction Unfinished nursing care (UNC), as the care required by patients that delayed or not delivered, has been investigated mainly from the perspective of nurses, while little is still known from the side of patients. Some studies have involved patients to measure which elements of care are mostly unfinished (e.g., mouth care), whereas a few studies have investigated the reasons for UNC as perceived by them. Their involvement in understanding the reasons for UNC is crucial to advance the knowledge and co‐develop possible strategies to prevent or minimize UNC. Methods This is a descriptive qualitative study performed according to COnsolidated criteria for REporting Qualitative research guidelines in 2022. A purposeful sample of Italian hospitalized patients in two medical and two surgical units was involved. A face‐to‐face semistructured interview was used to merge reasons for UNC. Qualitative content analysis was conducted to merge subthemes and themes as factors leading to UNC according to the experience of patients. Results A total of 23 patients (12 surgical and 11 medical) were involved (12/23 male) with an age average of 66.2 years, educated mainly at secondary school, and with previous hospitalizations (20/23), and dependent on nursing care in daily activities (14/23). Reasons for UNC have been identified at four levels: (1) 'New health‐care system priorities' and 'Pre‐existing frailty of health‐care facilities' were reasons identified at the health‐care system level; (2) 'Lack of resources attributed to wards', 'Ineffective ward organization' and 'Leadership' were identified at the unit level; (3) 'Nurses' attitudes and behaviour' were reported at the nurses' level and (4) 'Increased nursing care expectations' were pinpointed at the patient level. Conclusion Patients can be involved in identifying UNC, but also in recognizing the underlying reasons. Engaging them in such investigations might broaden our understanding of the phenomenon and the possibility of identifying strategies to minimize and prevent UNC. Patient or Public Contribution Patients from four hospital units (two medical and two surgical) were involved in face‐to‐face interviews to merge the reasons perceived by them as triggering UNC. All factors (as themes and subthemes) have derived from their words, thus enhancing the evidence available from the side of the patients.